Nanoscale ZSM-5 molecular sieve and preparation method thereof
By controlling the molar ratio of materials and adopting appropriate crystallization treatment, combined with the use of stabilizers, the preparation process of nano-scale ZSM-5 molecular sieve is simplified, and the problems of complex, time-consuming and cost-effective preparation of nano-scale ZSM-5 molecular sieve in the prior art are solved, and the preparation of high-efficiency and low-cost nano-scale ZSM-5 molecular sieve is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202311414516.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art has complex crystallization process, time-consuming, high equipment investment and large wastewater treatment burden when preparing nanoscale ZSM-5 molecular sieves, making it difficult to achieve large-scale industrial production.
By controlling the material molar ratio during the seed gel preparation process, using static and dynamic crystallization treatment, combined with an appropriate amount of stabilizer, simplifying the preparation steps, reducing costs, and achieving efficient preparation of nano-scale ZSM-5 molecular sieve.
It realizes efficient preparation of nanoscale ZSM-5 molecular sieve, adjustable particle size and simple steps, avoiding the use of a large number of expensive quaternary ammonium alkali template agents and silicone sources, and is suitable for industrial production.
Smart Images

Figure CN119898791A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of zeolite molecular sieve synthesis, and in particular, to a nano-scale ZSM-5 molecular sieve and a preparation method thereof. Background Art
[0002] Zeolite molecular sieves are a type of crystalline material with a specific pore structure. Due to their rich pore structure, large specific surface area and adjustable acidity, this type of material is widely used in the fields of petroleum refining and petrochemicals.
[0003] ZSM-5 molecular sieve is a zeolite molecular sieve with MFI topology, and its pore structure is composed of straight and sinusoidal pores. Thanks to the unique pore structure of ZSM-5 molecular sieve, ZSM-5 molecular sieve has good shape selectivity, so ZSM-5 molecular sieve is widely used in catalytic fields such as catalytic cracking, light hydrocarbon aromatization, alkylation and methanol conversion. However, in reactions involving large molecules or liquid phases, ZSM-5 molecular sieves with conventional crystal sizes have small pore sizes, long diffusion paths, and large diffusion resistance. Carbon deposits are easily formed inside the pores of the molecular sieve, which in turn blocks the pores and causes carbon deposits to deactivate.
[0004] Reducing the particle size of molecular sieves is one of the effective ways to improve their resistance to carbon deposition and deactivation. Compared with traditional micron-sized molecular sieves, small crystals or nano-sized molecular sieves have the advantages of shorter diffusion paths, larger external specific surface areas, and higher intracrystalline diffusion rates. However, it is still a challenge to prepare nano-sized ZSM-5 molecular sieves using low-cost and simple methods.
[0005] Patent CN105585028B discloses a method for synthesizing small-grain nano-zeolite molecular sieves. Its technical feature is that the size of the ZSM-5 molecular sieve is controlled by adopting a three-stage crystallization method and controlling the crystallization temperature of each stage. The disadvantage of this synthesis method is that the crystallization stage is too complicated and time-consuming, making it difficult to achieve industrial application.
[0006] Patent CN102502696B discloses a method for synthesizing ZSM-5 zeolite. Its technical feature is that the silicon source and aluminum source are pre-treated with acid or alkali in advance to depolymerize them into oligomeric or monomeric high-activity silicate and aluminate, and ZSM-5 molecular sieve is prepared on this basis. The disadvantage of this synthesis method is that a large amount of acid and alkali solution is required to pre-treat the raw materials, which brings a huge burden to the wastewater treatment of industrial production and is difficult to achieve industrial application.
[0007] Patent CN102745714B discloses a method for preparing a small-grain ZSM-5 molecular sieve. Its technical feature is that the organosilicon source is first dispersed in an alcohol solution, so that the alcohol solution containing the organosilicon source does not need a long hydrolysis process after being mixed with an inorganic alkaline solution containing a template agent, thereby avoiding the defects of a long and complicated preparation process of the ZSM-5 molecular sieve. The disadvantage of this synthesis method is that it requires the use of an expensive organosilicon source.
[0008] Patent CN102874843B discloses a rapid synthesis method of nano-scale ZSM-5 molecular sieve. Its technical feature is that a prepared dry glue seed is added during the preparation of the ZSM-5 molecular sieve, thereby inducing the rapid formation of molecular sieve crystals during the crystallization process. The disadvantage of this synthesis method is that the seed glue will cause the growth of crystal nuclei during the high-temperature drying process, thereby making the prepared ZSM-5 molecular sieve grains larger.
[0009] Patent CN109694087B discloses a method for synthesizing nano ZSM-5 molecular sieve aggregates. Its technical feature is that a mixture of an acidified aluminum source and an alkaline silicon source is evenly dispersed by ultrasonic oscillation to prepare ZSM-5 molecular sieve aggregates with a primary particle size of 20-50 nm. The disadvantage of this synthesis method is that it requires the use of ultrasonic equipment, which increases equipment investment and is not conducive to large-scale industrial promotion.
[0010] Patent CN105836756B discloses a method for synthesizing ZSM-5 molecular sieves. Its technical feature is that a small amount of ZSM-5 micronuclear sol is used instead of a large amount of traditional organic templates to induce the synthesis of high-quality monodisperse regular crystalline ZSM-5 molecular sieves. The disadvantage of this synthesis method is that the particle size of ZSM-5 molecular sieves is relatively large, belonging to the micron level.
[0011] In summary, although the existing technology can successfully prepare nano-scale ZSM-5 molecular sieves, there are still many problems in the preparation process: the synthesis process requires the use of specific templates, silicon sources or aluminum sources; the synthesis process requires the use of a large amount of expensive quaternary ammonium base templates and organic silicon sources; the synthesis process requires the use of microwave or ultrasound-assisted synthesis, etc. These problems are not conducive to industrial large-scale production. Summary of the invention
[0012] The purpose of the present disclosure is to provide a preparation method of nano-scale ZSM-5 molecular sieve and the preparation method thereof, which has low cost, simple steps and is easy to industrialize.
[0013] In order to achieve the above object, the present disclosure provides a method for preparing a nanoscale ZSM-5 molecular sieve in a first aspect, the method comprising the following steps:
[0014] S1, bringing a first template, a first silicon source and water into first contact, and performing a first crystallization treatment on a first material obtained by the first contact to obtain a seed glue;
[0015] S2, subjecting the alkali source, water, the second template, the second silicon source, the aluminum source, the seed glue and the optional stabilizer to a second contact, and subjecting the second material obtained by the second contact to a second crystallization treatment and a third crystallization treatment;
[0016] In step S1, the molar ratio of the first silicon source to the water is 1:(4-15) in terms of SiO2;
[0017] The molar ratio of the first template to the first silicon source calculated as SiO2 is greater than 0.35;
[0018] The stabilizer includes a nitrogen-containing organic compound.
[0019] Optionally, in step S1, the molar ratio of the first template to the first silicon source calculated as SiO2 is (0.35-0.60):1;
[0020] Optionally, in step S1, the molar ratio of the first silicon source calculated as SiO2 to the water is 1:(4.5-9).
[0021] Optionally, in step S1, the first crystallization treatment is performed by static crystallization, and the conditions include: time of 12-96 hours, preferably 48-96 hours; temperature of 60-100°C, preferably 60-70°C.
[0022] Optionally, the first silicon source includes one or more of organic silicon sources, preferably tetraethyl orthosilicate and / or tetrabutyl orthosilicate;
[0023] The first template agent includes one or more of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide and tetraethylammonium hydroxide;
[0024] The second silicon source includes one or more of an inorganic silicon source and an organic silicon source, preferably includes one or more of silica gel powder, white carbon black and silica sol;
[0025] The alkaline source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water;
[0026] The aluminum source includes one or more of aluminum isopropoxide, sodium metaaluminate, aluminum sulfate and aluminum chloride;
[0027] The second template comprises one or more of aliphatic amines having 2 to 4 carbon atoms, preferably one or more of ethylamine, n-propylamine and n-butylamine;
[0028] The stabilizer includes one or more of amine polymers, fatty amines with carbon atoms of 5-7 and organic ammonium salts with carbon atoms of 18-20, preferably one or more of polyethyleneimine, 1,6-hexanediamine and hexadecyltrimethylammonium bromide.
[0029] Optionally, in step S2, the second crystallization process and the third crystallization process are respectively performed by static crystallization or dynamic crystallization;
[0030] The conditions of the second crystallization treatment include: a time of 24-72 hours, preferably 24-48 hours; a temperature of 60-100° C., preferably 70-80° C.;
[0031] The conditions of the third crystallization treatment include: time of 4-36 hours, preferably 4-24 hours; temperature of 155-220°C, preferably 160-180°C.
[0032] Optionally, in step S2, in the second material, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, alkali metal element calculated as metal oxide, the second template and H2O is 100:(1-2):(10-20):(5-25):(400-3000);
[0033] Relative to the total weight of the second material, the stabilizer is added in an amount of 1-8% by weight.
[0034] Optionally, in step S2, in the second material, the amount of seed glue calculated as SiO2 is 1-9 mol%, preferably 1-7 mol%, relative to the total molar amount of silicon element calculated as SiO2.
[0035] Optionally, the method further comprises: heat treating the solid obtained by the third crystallization process;
[0036] The heat treatment method includes roasting, and the conditions include: temperature of 500-650° C. and time of 4-6 hours.
[0037] The second aspect of the present disclosure provides a nano-sized ZSM-5 molecular sieve prepared by the method described in the first aspect of the present disclosure.
[0038] Optionally, the primary crystal size of the nano-scale ZSM-5 molecular sieve is 40-250 nm, preferably 40-200 nm; and the relative crystallinity is 70-95%.
[0039] Through the above technical scheme, the method can prepare nano-scale ZSM-5 molecular sieves by controlling the molar ratio of materials in the seed gel preparation process. The particle size is adjustable and the steps are simple. It avoids the use of a large amount of expensive quaternary ammonium base templates and silicone sources and is easy to industrialize.
[0040] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0042] Figure 1 is the XRD spectrum of the ZSM-5 molecular sieve A1 of Example 1 of the present disclosure;
[0043] Figure 2 This is a SEM image of the ZSM-5 molecular sieve A1 of Example 1 of the present disclosure;
[0044] Figure 3 This is a SEM image of the ZSM-5 molecular sieve A2 of Example 2 of the present disclosure;
[0045] Figure 4 This is a SEM image of the ZSM-5 molecular sieve A3 of Example 3 of the present disclosure;
[0046] Figure 5 This is a SEM image of the ZSM-5 molecular sieve A4 of Example 4 of the present disclosure;
[0047] Figure 6 This is a SEM image of the ZSM-5 molecular sieve A5 of Example 5 of the present disclosure;
[0048] Figure 7 This is a SEM image of the ZSM-5 molecular sieve A6 of Example 6 of the present disclosure;
[0049] Figure 8 This is a SEM image of the ZSM-5 molecular sieve A7 of Example 7 of the present disclosure;
[0050] Fig. 9 This is a SEM image of the ZSM-5 molecular sieve A8 of Example 8 of the present disclosure;
[0051] Fig.10 This is a SEM image of the ZSM-5 molecular sieve A9 of Example 9 of the present disclosure;
[0052] Fig.11 is a SEM image of the ZSM-5 molecular sieve A10 of Example 10 of the present disclosure;
[0053] Fig.12 This is a SEM image of the ZSM-5 molecular sieve A11 of Example 11 of the present disclosure;
[0054] Fig.13 This is a SEM image of the ZSM-5 molecular sieve A12 of Example 12 of the present disclosure;
[0055] Fig.14 This is a SEM image of the ZSM-5 molecular sieve A13 of Example 13 of the present disclosure;
[0056] Fig.15 This is a SEM image of the ZSM-5 molecular sieve A14 of Example 14 of the present disclosure;
[0057] Fig.16 This is a SEM image of the ZSM-5 molecular sieve A15 of Example 15 of the present disclosure;
[0058] Fig.17 This is a SEM image of the ZSM-5 molecular sieve A16 of Example 16 of the present disclosure;
[0059] Fig.18 This is a SEM image of the ZSM-5 molecular sieve A17 of Example 17 of the present disclosure;
[0060] Fig.19 This is a SEM image of the ZSM-5 molecular sieve A18 of Example 18 of the present disclosure;
[0061] Fig. 20 This is a SEM image of the ZSM-5 molecular sieve D1 of Comparative Example 1 of the present disclosure;
[0062] Fig.21 is the XRD pattern of the ZSM-5 molecular sieve D2 of Comparative Example 2 of the present disclosure;
[0063] Fig. 22 This is the XRD diagram of the ZSM-5 molecular sieve D3 of Comparative Example 3 of the present disclosure. DETAILED DESCRIPTION
[0064] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0065] The first aspect of the present disclosure provides a method for preparing a nanoscale ZSM-5 molecular sieve, the method comprising the following steps:
[0066] S1, bringing a first template, a first silicon source and water into first contact, and performing a first crystallization treatment on a first material obtained by the first contact to obtain a seed glue;
[0067] S2, subjecting the alkali source, water, the second template, the second silicon source, the aluminum source, the seed glue and the optional stabilizer to a second contact, and subjecting the second material obtained by the second contact to a second crystallization treatment and a third crystallization treatment;
[0068] In step S1, the molar ratio of the first silicon source to the water is 1:(4-15) in terms of SiO2;
[0069] The molar ratio of the first template to the first silicon source calculated as SiO2 is greater than 0.35;
[0070] The stabilizer includes a nitrogen-containing organic compound.
[0071] The seed gel prepared by the method disclosed in the present invention can be observed to have an obvious Tyndall effect by irradiation with light, indicating that the number of crystal nuclei in the seed gel is large, which can reduce the particle size of the prepared ZSM-5 molecular sieve; and the method disclosed in the present invention can control the particle size of the ZSM-5 molecular sieve by adjusting the proportion of water in step S1; when a stabilizer is added to the synthesis system, it can play a role in hindering gel agglomeration and further reduce the particle size of the molecular sieve.
[0072] In the present disclosure, if some raw materials in step S1 contain water and the ratio of water to other raw materials is not within the scope of the present disclosure, the water can be evaporated by heating until the molar ratio of water to other raw materials is within the scope of the present application. To ensure that the water is evaporated without losing the raw materials, the heating temperature can be, for example, 30-60°C.
[0073] According to one embodiment of the present disclosure, in step S1, the molar ratio of the first template to the first silicon source calculated as SiO2 is (0.35-0.60):1, preferably (0.40-0.50):1.
[0074] According to one embodiment of the present disclosure, in step S1, the molar ratio of the first silicon source calculated as SiO2 to water is 1:(4.5-9); the above range can increase the number of crystal nuclei in the seed colloid and further reduce the particle size of the ZSM-5 molecular sieve.
[0075] According to one embodiment of the present disclosure, in step S1, the first crystallization treatment is static crystallization, and the conditions include: time is 12-96h, preferably 48-96h; temperature is 60-100°C, preferably 60-70°C; the above-mentioned first crystallization treatment conditions can increase the number of crystal nuclei in the seed gel and further reduce the particle size of the ZSM-5 molecular sieve.
[0076] According to one embodiment of the present disclosure, the first silicon source includes one or more of the organic silicon sources, preferably includes one or more of the silicates with a carbon number of 8-16, more preferably tetraethyl orthosilicate (CAS: 78-10-4) and / or tetrabutyl orthosilicate (CAS: 4766-57-8). When the first silicon source includes more than two types, there is no specific limitation on their ratio; the first silicon source can be, for example, tetraethyl orthosilicate.
[0077] According to one embodiment of the present disclosure, the type of the first template is conventional in the art, for example, it may include one or more of an organic ammonium hydroxide having a carbon number of 4-12 and an organic ammonium salt having a carbon number of 8-12, preferably one or more of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide and tetraethylammonium hydroxide. When the first template includes more than two types, there is no specific limitation on the ratio thereof; the first template may be, for example, tetrapropylammonium hydroxide.
[0078] According to one embodiment of the present disclosure, the second silicon source includes one or more of an inorganic silicon source and an organic silicon source, preferably includes one or more of the inorganic silicon sources, and further preferably includes one or more of silica gel powder, white carbon black and silica sol. When the second silicon source includes more than two types, there is no specific restriction on their proportion. The second silicon source can be, for example, silica gel powder. Using an inorganic silicon source as the second silicon source in step S2 can reduce the usage of the organic silicon source in the overall preparation process and further reduce costs.
[0079] According to one embodiment of the present disclosure, the type of alkali source is conventional in the art, for example, it may include one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water. When the alkali source includes more than two types, there is no specific limitation on their ratio.
[0080] According to one embodiment of the present disclosure, the aluminum source includes one or more of aluminum isopropoxide, sodium aluminate, aluminum sulfate and aluminum chloride. When the aluminum source includes more than two types, there is no specific limitation on their ratio. The aluminum source can be, for example, sodium aluminate.
[0081] According to one embodiment of the present disclosure, the second template includes one or more of the fatty amines having a carbon number of 2-4, preferably including one or more of ethylamine, n-propylamine and n-butylamine. When the second template includes more than two types, there is no specific limitation on the ratio thereof; the second template can be, for example, n-butylamine.
[0082] According to one embodiment of the present disclosure, the stabilizer includes one or more of an amine polymer, a fatty amine with a carbon number of 5-7 and an organic ammonium salt with a carbon number of 18-20, wherein the number of amino groups in the fatty amine can be 1 or 2, and the organic ammonium salt can be an organic quaternary ammonium salt; the stabilizer preferably includes one or more of polyethyleneimine, 1,6-hexanediamine and hexadecyltrimethylammonium bromide. When the stabilizer is a polymer, there is no specific limitation on its molecular weight.
[0083] According to an embodiment of the present disclosure, in step S2, the second crystallization treatment and the third crystallization treatment are respectively static crystallization or dynamic crystallization; the conditions of the second crystallization treatment include: time is 24-72h, preferably 24-48h; temperature is 60-100℃, preferably 70-80℃; the conditions of the third crystallization treatment include: time is 4-36h, preferably 4-24h; temperature is 155-220℃, preferably 160-180℃; the present disclosure adopts two-stage crystallization in step S2 of preparing molecular sieve to control nucleation and growth rate, the above-mentioned second crystallization treatment can promote the depolymerization of aggregated silicon source, avoid pretreatment of silicon source, and is conducive to further nucleation, while the third crystallization process can promote the growth of crystal nuclei and improve the single-pot yield.
[0084] In the present disclosure, the operation steps of dynamic crystallization and static crystallization are conventional in the art.
[0085] According to one embodiment of the present disclosure, in step S2, in the second material, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, alkali metal element calculated as metal oxide, the second template and H2O is 100:(1-2):(10-20):(5-25):(400-3000), preferably 100:(1-1.8):(10-25):(10-24):(500-1000); wherein, the "molar amount of H2O" includes the water added in step S2, the water in the seed gel and the H2O in the alkali source calculated according to the chemical formula, for example, the alkali source is 1 mol of NaOH, in which the H2O is 0.5 mol; the molar amount of the second template is based on the added second template.
[0086] According to one embodiment of the present disclosure, in step S2, the amount of stabilizer added is 1-8% by weight, preferably 1-5% by weight, relative to the total weight of the second material. The addition of the stabilizer can further reduce the particle size of the ZSM-5 molecular sieve.
[0087] According to one embodiment of the present disclosure, in step S2, in the second material, the amount of seed glue calculated as SiO2 relative to the total molar amount of silicon element calculated as SiO2 is 1-9 mol%, preferably 1-7 mol%, and the above-mentioned amount of seed glue added can further reduce the preparation cost and the primary grain size; wherein, "the amount of seed glue calculated as SiO2 relative to the total molar amount of silicon element calculated as SiO2" refers to the proportion of silicon element calculated as SiO2 added through the seed glue relative to the total molar amount of silicon element calculated as SiO2 in the second material system.
[0088] According to an embodiment of the present disclosure, the present disclosure does not specifically limit the order of adding the materials in step S2, and for example, the following steps may be included:
[0089] a. Mixing an alkali source, a second template and water;
[0090] b. mixing a second silicon source and an aluminum source with the mixture obtained in step a;
[0091] c. Mixing the seed glue with the mixture obtained in step b; optionally, adding a stabilizer to the mixture obtained in step c.
[0092] According to an embodiment of the present disclosure, the method further comprises: heat treating the solid obtained by the third crystallization treatment; the heat treatment comprises calcination, and the conditions comprise: temperature of 500-650°C and time of 4-6h.
[0093] According to one embodiment of the present disclosure, the method further includes: filtering the mixed material obtained by the third crystallization treatment, washing and drying the obtained solid, and then performing heat treatment; the above-mentioned filtering, washing and drying treatment methods and conditions are conventional in the art, for example, the drying treatment temperature is 80-120°C, and the time is 4-24h.
[0094] In the present disclosure, all crystallization processes can be performed in a closed reactor.
[0095] The second aspect of the present disclosure provides a nano-sized ZSM-5 molecular sieve prepared by the method described in the first aspect of the present disclosure.
[0096] According to one embodiment of the present disclosure, the primary crystallite size of the nano-sized ZSM-5 molecular sieve is 40-250 nm, preferably 40-200 nm.
[0097] According to one embodiment of the present disclosure, the relative crystallinity is 70-95%.
[0098] The present invention is further described in detail below by examples, but the present invention is not limited thereto.
[0099] The raw materials used in the examples are as follows:
[0100] Silica gel powder: special silica gel powder for marine chemical industry.
[0101] Sodium aluminate: Shandong Lier New Materials Co., Ltd.
[0102] n-Butylamine: 99% by weight, Beijing Inokai Technology Co., Ltd.
[0103] Tetraethyl orthosilicate (CAS: 78-10-4, molecular weight 208.33): 98 wt%, aladdin.
[0104] Tetrapropylammonium hydroxide: water content is 25% by weight, Beijing Inokai Technology Co., Ltd.
[0105] Tetrabutyl orthosilicate (CAS: 4766-57-8, molecular weight 320.55): 98% by weight, aladdin.
[0106] Tetrapropylammonium bromide: 98% by weight, Macklin.
[0107] Potassium hydroxide: 99% by weight, Macklin.
[0108] Silica sol: special silica gel powder for marine chemical industry.
[0109] n-Propylamine: 98% by weight, Macklin.
[0110] Aluminum isopropoxide: 99 wt%, Macklin.
[0111] The physicochemical properties of the ZSM-5 molecular sieve in the examples are tested as follows:
[0112] Relative crystallinity: The relative crystallinity is expressed by the ratio of the sum of the heights of five XRD diffraction peaks at 2θ angles of 22.5-25.0° in the X-ray diffraction (XRD) spectra of the product and the comparative example.
[0113] Primary grain size: The molecular sieve morphology was measured using a FEI Quanta 3D FEG scanning electron microscope with an acceleration voltage of 20 kV.
[0114] Example 1
[0115] Nano-sized ZSM-5 molecular sieve A1 was prepared by the following steps:
[0116] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and statically crystallize at 70°C for 24 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0117] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.8 g of silica gel powder, 8.3 g of n-butylamine, 7.8 g of the seed glue prepared in step (1), and 73.0 g of water;
[0118] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A1 is obtained by cooling, filtering, washing, drying and calcining.
[0119] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0120] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 3 mol%;
[0121] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0122] XRD test was performed on ZSM-5 molecular sieve A1, and the results are as follows Figure 1 As shown, it can be seen that diffraction peaks appear at 7.9°, 8.7°, 23.1°, 23.9° and 24.4°, indicating that the molecular sieve is ZSM-5 molecular sieve. After calculation, the relative crystallinity is 89.9%;
[0123] The SEM test results of ZSM-5 molecular sieve A1 are as follows: Figure 2 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 180-200nm.
[0124] Example 2
[0125] Nano-sized ZSM-5 molecular sieve A2 was prepared by the following steps:
[0126] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and statically crystallize at 70°C for 48 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0127] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.8 g of silica gel powder, 8.3 g of n-butylamine, 7.8 g of the seed glue prepared in step (1), and 73.0 g of water;
[0128] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A2 is obtained by cooling, filtering, washing, drying and calcining.
[0129] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0130] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 3 mol%;
[0131] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0132] The XRD test of ZSM-5 molecular sieve A2 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 89.0%.
[0133] The SEM test results of ZSM-5 molecular sieve A2 are as follows: Figure 3 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 160-180nm.
[0134] Example 3
[0135] Nano-sized ZSM-5 molecular sieve A3 was prepared by the following steps:
[0136] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 72 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0137] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.8 g of silica gel powder, 8.3 g of n-butylamine, 7.8 g of the seed glue prepared in step (1), and 73.0 g of water;
[0138] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A3 is obtained by cooling, filtering, washing, drying and calcining.
[0139] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0140] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 3 mol%;
[0141] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0142] The XRD test of ZSM-5 molecular sieve A3 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve is ZSM-5 molecular sieve. The relative crystallinity is calculated to be 88.6%.
[0143] The SEM test results of ZSM-5 molecular sieve A3 are as follows: Figure 4 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 150-170nm.
[0144] Example 4
[0145] Nano-sized ZSM-5 molecular sieve A4 was prepared by the following steps:
[0146] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0147] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.8 g of silica gel powder, 8.3 g of n-butylamine, 7.8 g of the seed glue prepared in step (1), and 73.0 g of water;
[0148] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A4 is obtained by cooling, filtering, washing, drying and calcining.
[0149] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0150] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 3 mol%;
[0151] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0152] The XRD test of ZSM-5 molecular sieve A4 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 88.2%.
[0153] The SEM test results of ZSM-5 molecular sieve A4 are as follows: Figure 5 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 130-150nm.
[0154] Example 5
[0155] Nano-sized ZSM-5 molecular sieve A5 was prepared by the following steps:
[0156] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0157] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.1 g of silica gel powder, 8.3 g of n-butylamine, 13.1 g of the seed glue prepared in step (1), and 71.2 g of water;
[0158] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A5 is obtained by cooling, filtering, washing, drying and calcining.
[0159] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0160] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 5 mol%;
[0161] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0162] The XRD test of ZSM-5 molecular sieve A5 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve is ZSM-5 molecular sieve. The relative crystallinity is calculated to be 80.3%.
[0163] The SEM test results of ZSM-5 molecular sieve A5 are as follows: Figure 6 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 100-120nm.
[0164] Example 6
[0165] Nano-sized ZSM-5 molecular sieve A6 was prepared by the following steps:
[0166] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0167] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 34.4 g of silica gel powder, 8.3 g of n-butylamine, 18.3 g of the seed glue prepared in step (1), and 69.4 g of water;
[0168] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A6 is obtained by cooling, filtering, washing, drying and calcining.
[0169] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0170] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 7 mol%;
[0171] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0172] The XRD test of ZSM-5 molecular sieve A6 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve is ZSM-5 molecular sieve. The relative crystallinity is calculated to be 79.1%.
[0173] The SEM test results of ZSM-5 molecular sieve A6 are as follows: Figure 7 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 90-110nm.
[0174] Example 7
[0175] Nano-sized ZSM-5 molecular sieve A7 was prepared by the following steps:
[0176] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0177] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 33.6 g of silica gel powder, 8.3 g of n-butylamine, 23.6 g of the seed glue prepared in step (1), and 67.7 g of water;
[0178] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first statically crystallized at 70°C for 48 hours, and then statically crystallized at 170°C for 12 hours. After the crystallization is completed, the ZSM-5 molecular sieve A7 is obtained by cooling, filtering, washing, drying and calcining.
[0179] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0180] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 9 mol%.
[0181] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0182] The XRD test of ZSM-5 molecular sieve A7 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 79.8%.
[0183] The SEM test results of ZSM-5 molecular sieve A7 are as follows: Figure 8 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 90-110nm.
[0184] Example 8
[0185] Nano-sized ZSM-5 molecular sieve A8 was prepared by the following steps:
[0186] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0187] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.1 g of silica gel powder, 8.3 g of n-butylamine, 13.0 g of the seed glue prepared in step (1), and 71.2 g of water;
[0188] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first dynamically crystallized at 70°C for 48 hours, and then dynamically crystallized at 170°C for 24 hours. After the crystallization is completed, the ZSM-5 molecular sieve A8 is obtained by cooling, filtering, washing, drying and calcining.
[0189] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0190] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 5 mol%;
[0191] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0192] The ZSM-5 molecular sieve A8 was subjected to XRD test. Diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. After calculation, the relative crystallinity was 86.8%.
[0193] The SEM test results of ZSM-5 molecular sieve A8 are as follows: Fig. 9 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 80-100nm.
[0194] Example 9
[0195] Nano-sized ZSM-5 molecular sieve A9 was prepared by the following steps:
[0196] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0197] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.1 g of silica gel powder, 8.3 g of n-butylamine, 13.0 g of the seed glue prepared in step (1), and 71.2 g of water;
[0198] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor, first dynamically crystallized at 70°C for 48 hours, and then dynamically crystallized at 180°C for 24 hours. After the crystallization is completed, the ZSM-5 molecular sieve A9 is obtained by cooling, filtering, washing, drying and calcining.
[0199] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0200] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 5 mol%.
[0201] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0202] The XRD test of ZSM-5 molecular sieve A9 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 89.9%.
[0203] The SEM test results of ZSM-5 molecular sieve A9 are as follows: Fig.10 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 110-130nm.
[0204] Example 10
[0205] Nano-scale ZSM-5 molecular sieve A10 was prepared by the following steps:
[0206] (1) Weigh 55 g of tetraethyl orthosilicate and 96.7 g of tetrapropylammonium hydroxide (water content: 25 wt%), mix the two at 45°C to evaporate part of the water, and the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 is 1:0.46:9. Transfer the obtained mixture to a closed reactor and perform static crystallization at 70°C for 96 hours. After the crystallization is completed, cool down to obtain a seed glue;
[0207] (2) Weigh 4.4 g of sodium hydroxide, 2.5 g of sodium aluminate, 35.1 g of silica gel powder, 8.3 g of n-butylamine, 13.0 g of the seed glue prepared in step (1), and 71.2 g of water;
[0208] Under stirring, sodium hydroxide, n-butylamine and water are mixed. Then, silica gel powder and sodium aluminate are added thereto respectively. Finally, the seed glue prepared in step (1) is added. After the mixture is fully mixed, the mixture is transferred to a closed reactor and first subjected to dynamic crystallization at 70°C for 24 hours, and then to dynamic crystallization at 180°C for 24 hours. After the crystallization is completed, the ZSM-5 molecular sieve A10 is obtained by cooling, filtering, washing, drying and calcining.
[0209] In the mixture, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, sodium element calculated as Na2O, n-butylamine, and H2O is 100:1.4:12:20:900;
[0210] Relative to the total molar amount of SiO2 in the final synthesis system, the SiO2 added through the seed glue accounts for 5 mol%.
[0211] The drying temperature is 100°C and the time is 12h; the calcination temperature is 550°C and the time is 4h.
[0212] The ZSM-5 molecular sieve A10 was subjected to XRD test. Diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve is ZSM-5 molecular sieve. After calculation, the relative crystallinity is 87.3%.
[0213] The SEM test results of ZSM-5 molecular sieve A10 are as follows: Fig.11 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 90-110nm.
[0214] Embodiment 11
[0215] ZSM-5 molecular sieve A11 was prepared by the method of Example 10, except that polyethyleneimine was added as a stabilizer in step (2), and the amount of the stabilizer added was 1.5 wt % relative to the total weight of the mixture.
[0216] The XRD test of ZSM-5 molecular sieve A11 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 85.8%.
[0217] The SEM test results of ZSM-5 molecular sieve A11 are as follows: Fig.12 As shown, according to the results, the primary grains present a tetragonal morphology and the size of the primary grains is 60-70nm.
[0218] Example 12
[0219] ZSM-5 molecular sieve A12 was prepared by the method of Example 10, except that 1,6-hexanediamine was added as a stabilizer in step (2), and the amount of the stabilizer added was 1.5 wt % relative to the total weight of the mixture.
[0220] The XRD test of ZSM-5 molecular sieve A12 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 86.5%.
[0221] The SEM test results of ZSM-5 molecular sieve A12 are as follows: Fig.13 As shown, according to the results, the primary grains present a tetragonal morphology and the size of the primary grains is 80-90nm.
[0222] Embodiment 13
[0223] ZSM-5 molecular sieve A13 was prepared by the method of Example 10, except that hexadecyltrimethylammonium bromide was added as a stabilizer in step (2), and the amount of the stabilizer added was 1.5 wt % relative to the total weight of the mixture.
[0224] The ZSM-5 molecular sieve A13 was subjected to XRD test. In the XRD spectrum, diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4°, indicating that the molecular sieve was ZSM-5 molecular sieve. After calculation, the relative crystallinity was 73.0%.
[0225] The SEM test results of ZSM-5 molecular sieve A13 are as follows: Fig.14 As shown, according to the results, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 80-100nm.
[0226] Embodiment 14
[0227] ZSM-5 molecular sieve A14 was prepared by the method of Example 10, except that in step (1), the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water was 1:0.46:4.5, and in step (2), polyethyleneimine was added as a stabilizer in an amount of 2.4 wt % relative to the total weight of the mixture.
[0228] The XRD test of ZSM-5 molecular sieve A14 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 85.3%.
[0229] The SEM test results of ZSM-5 molecular sieve A14 are as follows: Fig.15 As shown, according to the results, the primary grains present a tetragonal morphology and the size of the primary grains is 50-70nm.
[0230] Embodiment 15
[0231] ZSM-5 molecular sieve A15 was prepared by the method of Example 14, except that in step (2), the amount of polyethyleneimine added was 3.2 wt % relative to the total weight of the mixture.
[0232] The XRD test of ZSM-5 molecular sieve A15 showed that diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum, indicating that the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 85.0%.
[0233] The SEM test results of ZSM-5 molecular sieve A15 are as follows: Fig.16 As shown, according to the results, the primary grains present a tetragonal morphology and the size of the primary grains is 40-60nm.
[0234] Example 16
[0235] The method of Example 1 was used to prepare ZSM-5 molecular sieve A16, except that:
[0236] In step (1), tetraethyl orthosilicate is replaced by tetrabutyl orthosilicate containing an equal mole of SiO2, and tetrapropylammonium hydroxide is replaced by an equal mole of tetrapropylammonium bromide;
[0237] In step (2), sodium hydroxide is replaced by an equimolar amount of potassium hydroxide, silica gel powder is replaced by a silica sol containing an equimolar amount of SiO2, n-butylamine is replaced by an equimolar amount of propylamine, and sodium aluminate is replaced by aluminum isopropoxide containing an equimolar amount of Al2O3;
[0238] The ZSM-5 molecular sieve A16 was subjected to XRD test. Diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4° in the XRD spectrum. According to the results, the molecular sieve is ZSM-5 molecular sieve. After calculation, the relative crystallinity is 94.1%.
[0239] The SEM test results of ZSM-5 molecular sieve A16 are as follows: Fig.17 As shown, according to the results, the primary grains present a tetragonal morphology and the size of the primary grains is 170-200nm.
[0240] Embodiment 17
[0241] The method of Example 1 was used to prepare ZSM-5 molecular sieve A17, except that:
[0242] (1) The molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water, calculated on the basis of SiO2, is 1:0.46:15;
[0243] The XRD test of ZSM-5 molecular sieve A17 showed that the diffraction peaks appeared at 7.9°, 8.7°, 23.1°, 23.9° and 24.4°. According to the results, the molecular sieve was ZSM-5 molecular sieve. The relative crystallinity was calculated to be 93.1%.
[0244] The SEM test results of ZSM-5 molecular sieve A17 are as follows: Fig.18 As shown, it can be seen that the primary grains present a tetragonal morphology and the size of the primary grains is 190-220nm.
[0245] Embodiment 18
[0246] The method of Example 1 was used to prepare ZSM-5 molecular sieve A18, except that:
[0247] (1) The molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water is 1:0.6:9 based on SiO2;
[0248] The SEM test results of ZSM-5 molecular sieve D3 are as follows: Fig.19 As shown, it can be seen that the primary grains present a tetragonal morphology, and the size of the primary grains is 180-200nm;
[0249] The ZSM-5 molecular sieve A18 was subjected to XRD test, and the XRD spectrum showed diffraction peaks at 7.9°, 8.7°, 23.1°, 23.9° and 24.4°. According to the results, the molecular sieve was ZSM-5 molecular sieve, and the relative crystallinity was calculated to be 90.8%.
[0250] Comparative Example 1
[0251] The ZSM-5 molecular sieve D1 was prepared by the method of Example 1, except that the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 was 1:0.46:18. The ZSM-5 molecular sieve D1 was tested by XRD and SEM. The SEM test results are as follows: Fig. 20 As shown, the size of the primary crystallites is 220-260 nm, and according to XRD calculation, its relative crystallinity is 94.9%.
[0252] Comparative Example 2
[0253] ZSM-5 molecular sieve D2 was prepared by the method of Example 1, except that the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 was 1:0.46:2.5. XRD test was performed on ZSM-5 molecular sieve D2. The XRD test results are as follows: Fig.21As shown, according to Fig.21 It can be seen that the molecular sieve is not completely crystallized. After calculation, its relative crystallinity is 21.0%. It still appears gray-black after multiple calcinations, and a large amount of template agent cannot be removed from the gel.
[0254] Comparative Example 3
[0255] The method of Example 1 was used to prepare ZSM-5 molecular sieve D3, except that the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and water in terms of SiO2 was 1:0.2:9. XRD test was performed on ZSM-5 molecular sieve D4. The XRD test results are as follows: Fig. 22 As shown, according to Fig. 22 It can be seen that the molecular sieve is not completely crystallized. After calculation, its relative crystallinity is 16.5%. It still appears gray-black after multiple calcinations, and a large amount of template agent cannot be removed from the gel.
[0256] According to the above embodiments and comparative examples, it can be known that the method of the present invention can prepare nano-scale ZSM-5 molecular sieves with smaller grain sizes by controlling the amount of materials used; further, through the comparison of embodiments 1-4, it can be known that other conditions are the same, when the time of the first crystallization treatment is within the preferred range of the present invention, the grain size of the molecular sieve can be further reduced; through the comparison of embodiments 4-7, it can be known that other conditions are the same, when the amount of seed glue is within the preferred range of the present invention, the grain size of the molecular sieve can be further reduced while reducing the amount of seed glue; through the comparison of embodiments 10-13, it can be known that other conditions are the same, when a stabilizer is added in step S1, the grain size of the molecular sieve can be further reduced.
[0257] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0258] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0259] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a nano-scale ZSM-5 molecular sieve, characterized in that: The method comprises the following steps: S1, bringing a first template, a first silicon source and water into first contact, and performing a first crystallization treatment on a first material obtained by the first contact to obtain a seed glue; S2, subjecting the alkali source, water, the second template, the second silicon source, the aluminum source, the seed glue and the optional stabilizer to a second contact, and subjecting the second material obtained by the second contact to a second crystallization treatment and a third crystallization treatment; In step S1, the molar ratio of the first silicon source to the water is 1:(4-15) in terms of SiO2; The molar ratio of the first template to the first silicon source calculated as SiO2 is greater than 0.35; The stabilizer includes a nitrogen-containing organic compound.
2. The method according to claim 1, wherein: In step S1, the molar ratio of the first template to the first silicon source calculated as SiO2 is (0.35-0.60):1; Optionally, in step S1, the molar ratio of the first silicon source calculated as SiO2 to the water is 1:(4.5-9).
3. The method according to claim 1, wherein: In step S1, the first crystallization treatment is performed by static crystallization, and the conditions include: time of 12-96 hours, preferably 48-96 hours; temperature of 60-100°C, preferably 60-70°C.
4. The method according to claim 1, wherein: The first silicon source includes one or more of organic silicon sources, preferably tetraethyl orthosilicate and / or tetrabutyl orthosilicate; The first template agent includes one or more of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide and tetraethylammonium hydroxide; The second silicon source includes one or more of an inorganic silicon source and an organic silicon source, preferably includes one or more of silica gel powder, white carbon black and silica sol; The alkaline source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water; The aluminum source includes one or more of aluminum isopropoxide, sodium metaaluminate, aluminum sulfate and aluminum chloride; The second template comprises one or more of aliphatic amines having 2 to 4 carbon atoms, preferably one or more of ethylamine, n-propylamine and n-butylamine; The stabilizer includes one or more of amine polymers, fatty amines with carbon atoms of 5-7 and organic ammonium salts with carbon atoms of 18-20, preferably one or more of polyethyleneimine, 1,6-hexanediamine and hexadecyltrimethylammonium bromide.
5. The method according to claim 1, wherein: In step S2, the second crystallization process and the third crystallization process are respectively performed by static crystallization or dynamic crystallization; The conditions of the second crystallization treatment include: a time of 24-72 hours, preferably 24-48 hours; a temperature of 60-100° C., preferably 70-80° C.; The conditions of the third crystallization treatment include: time of 4-36 hours, preferably 4-24 hours; temperature of 155-220°C, preferably 160-180°C.
6. The method according to claim 1, wherein: In step S2, in the second material, the molar ratio of silicon element calculated as SiO2, aluminum element calculated as Al2O3, alkali metal element calculated as metal oxide, second template and H2O is 100:(1-2):(10-20):(5-25):(400-3000); Relative to the total weight of the second material, the stabilizer is added in an amount of 1-8% by weight.
7. The method according to claim 1, wherein: In step S2, in the second material, the amount of seed glue calculated as SiO2 is 1-9 mol%, preferably 1-7 mol%, relative to the total molar amount of silicon element calculated as SiO2.
8. The method according to claim 1, wherein: The method further comprises: heat treating the solid obtained by the third crystallization process; The heat treatment method includes roasting, and the conditions include: temperature of 500-650° C. and time of 4-6 hours.
9. Nano-scale ZSM-5 molecular sieve prepared by the method according to any one of claims 1 to 8.
10. The nano-scale ZSM-5 molecular sieve according to claim 9, wherein: The primary crystal size of the nano-scale ZSM-5 molecular sieve is 40-250 nm, preferably 40-200 nm; and the relative crystallinity is 70-95%.
Citation Information
Patent Citations
Synthetic method of ZSM-5 zeolites
CN102502696B
Preparation method of small crystal grain ZSM-5 molecular sieve
CN102745714B
Rapid Synthesis Method of Nanoscale ZSM-5 Molecular Sieves
CN102874843B
Synthesis method of small-grain nano-zeolite molecular sieve
CN105585028B
A method for preparing zsm-5 molecular sieves with monodisperse regular crystal morphology without template system
CN105836756B